Enhanced Lipofilling Outcomes Using Platelet-Rich Plasma: An Innovative Approach (Journal of Academic Research, 2025)
Introduction:Adipose tissue for autotransplantation is easily accessible. Due to comparatively variable and unexpected survival, the popularity of fat transfer surgery has fluctuated throughout the years. The outcome of autologous fat tissue grafts is influenced by numerous factors, some of which the surgeon can manage, like Aseptic procedures, low pressure suction, cautious handling of graft tissues, and the use of minimally traumatic cannulae. There is growing evidence that careful donor site selection and manipulation of specific healing mechanisms that regulate cellular recruitment, migration, and differentiation at the recipient site may improve the consistency and dependability of fat grafts.The purpose of this paper to investigate the improving the survivability and outcome of using transplanted fat with PRP as an alternative to soft tissue augmentation using only fat tissue transfer as the ordinary procedureMaterials and Methods:The study here is a preliminary clinical investigation combined with a description of a novel technique. It introduces a new method of enhancing autologous fat transplantation with platelet-rich plasma (PRP) and reports initial clinical observations.Results: A higher percentage of graft volume retention (about 91% of the volume of the transferred tissue after 6months post-surgery) appears to be produced following the use of these procedures with all the patients, and regarding to the complication, I observe that The percentage of secondary calcifications occurred in 4% of the patients, and microcyst formation was observed in 3% of them.
Keywords: Autologous fat transplantation; Platelet-rich plasma (PRP); Fat graft survivability; Soft tissue augmentation; Graft retention